Evans-Jones, Gareth. 2022. “Mae’r Beibl o’n tu”: Ymatebion crefyddol y Cymry yn America i gaethwasiaeth (1838-1868). Cardiff: Gwasg Prifysgol Cymru. [“The Bible’s on our side”: religious responses of Welsh people in America to slavery (1838-1868)] - Cleaves, Richard (Studia Celtica Posnaniensia, 2024)
Evans-Jones, Gareth. 2022. “Mae’r Beibl o’n tu”: Ymatebion crefyddol y Cymry yn America i gaethwasiaeth (1838-1868). Cardiff: Gwasg Prifysgol Cymru. [“The Bible’s on our side”: religious responses of Welsh people in America to slavery (1838-1868)]